2017
DOI: 10.1007/s12035-017-0635-y
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus as an Emerging Neuropathogen: Mechanisms of Neurovirulence and Neuro-Immune Interactions

Abstract: Zika virus (ZIKV) is an emerging arbovirus of the genus Flaviviridae, which causes a febrile illness and has spread from across the Pacific to the Americas in a short timeframe. Convincing evidence has implicated the ZIKV to incident cases of neonatal microcephaly and a set of neurodevelopmental abnormalities referred to as the congenital Zika virus syndrome. In addition, emerging data points to an association with the ZIKV and the development of the so-called Guillain-Barre syndrome, an acute autoimmune polyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 286 publications
0
20
0
4
Order By: Relevance
“…Additionally, the Asian strains of ZIKV indicates that a combination of factors, such as genetic variation in the NS5 gene as a result of mutations or recombination events and the reacquisition of a E-154 glycosylation motif, could contribute to neurovirulence. 183 Recent in vitro studies have shown that axonal changes occurred in the absence of overt infection or neuronal death. This suggests that axons could be injured by soluble or contactdependent factors in their environment.…”
Section: Chikungunya Virus and Gbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the Asian strains of ZIKV indicates that a combination of factors, such as genetic variation in the NS5 gene as a result of mutations or recombination events and the reacquisition of a E-154 glycosylation motif, could contribute to neurovirulence. 183 Recent in vitro studies have shown that axonal changes occurred in the absence of overt infection or neuronal death. This suggests that axons could be injured by soluble or contactdependent factors in their environment.…”
Section: Chikungunya Virus and Gbsmentioning
confidence: 99%
“…194 Noteworthy, the majority of GBS patients had evidence of prior DENV infection, 6 which makes the phenomenon of ADE a prime suspect, as far as the development of GBS in these patients is concerned. 183 In addition to DENV, a previous or coexistant infection with M. pneumoniae has been suggested as cofactor to GBS development in patients with ZIKV infection. 6 However, the above does not fully explain the apparent capacity of Asian lineages of ZIKV to trigger GBS in some patients, which appears to be lacking or greatly attenuated in the African strains.…”
Section: Chikungunya Virus and Gbsmentioning
confidence: 99%
“…71,74 Although ZIKV was first isolated in a rhesus monkey in 1947, there had only been 14 documented cases of human disease prior to 2007. 75 Since then, neurovirulent strains have emerged, and between 2007 and 2016, transmission was reported in South America, Central America, the Caribbean, Africa, Southeast Asia, and the western Pacific. 76 According to the Pan American Health Organization, as of August 25, 2017, 48 countries and territories in the Americas had confirmed vector-borne transmission of ZIKV and 5 countries in the Americas reported evidence of sexual transmission (►Fig.…”
Section: Zika Virusmentioning
confidence: 99%
“…Overall, The Culex mosquito and ducks have been implicated as a vector and a reservoir for DTMUV, respectively [10]. Although DTMUV has not been documented to cause human diseases, The potential risk for a virulent DTMUV strain infecting humans still exists.Many mosquito-borne flaviviruses, including The West Nile virus (WNV), Usutu virus (USUV), Japanese encephalitis virus (JEV), and Zika virus, are capable of causing severe neurological illness [11][12][13][14]. Similar to these flaviviruses, DTMUV is also neuroinvasive and neurovirulent, and can cause neurological symptoms.…”
mentioning
confidence: 99%
“…Many mosquito-borne flaviviruses, including The West Nile virus (WNV), Usutu virus (USUV), Japanese encephalitis virus (JEV), and Zika virus, are capable of causing severe neurological illness [11][12][13][14]. Similar to these flaviviruses, DTMUV is also neuroinvasive and neurovirulent, and can cause neurological symptoms.…”
mentioning
confidence: 99%